New star‐shaped phosphorus‐containing flame retardants based on acrylates for epoxy resins. (19th July 2013) - Müller, Patrick; Bykov, Yana; Döring, Manfred
Abstract : New star‐shaped phosphorus‐containing flame retardants were synthesized by phospha‐Michael‐addition of diphenylphosphine oxide and dimethyl phosphite to oligofunctional acrylates. The products were examined via UL 94 V‐rating and thermogravimetric analysis in three different epoxy resin systems compared to the recently described correspondent derivatives based on the phosphinate‐type 6‐oxido‐6H‐dibenzo[c, e][1, 2]oxaphosphinine. The influence of a systematically altered chemical environment of the phosphorus atom on the flame retardancy and the char yield was investigated. Furthermore, the glass transition temperatures of the modified resins were studied via differential scanning calorimetry, including the deviation after an additional treatment at elevated temperature. Copyright © 2013 John Wiley & Sons, Ltd.